2023
DOI: 10.3389/fonc.2023.1047644
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare coverage affects survival of EGFR-mutant Thai lung cancer patients

Abstract: BackgroundDespite significant benefits of epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment in patients with EGFR-mutated NSCLC, access remains limited in Thailand and elsewhere.MethodsRetrospective analysis of patients with locally advanced/recurrent NSCLC and known EGFR mutation (EGFRm) status treated at Ramathibodi Hospital (2012–2017). Prognostic factors for overall survival (OS), including treatment type and healthcare coverage, were analyzed using Cox regression.ResultsOf 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This improvement in survival rate could be explained by many factors, but in our study, the effect of TKI treatments for patients with expression of EGFR sensitizing mutations on mortality-risk reduction were observed in all analyses. This finding was consistent with the outcomes of a multicenter study in Thailand, which showed that EGFR-TKI treatment improved the overall survival of patients with EGFR-responsive mutations (Sukauichai et al, 2022;Khiewngam et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This improvement in survival rate could be explained by many factors, but in our study, the effect of TKI treatments for patients with expression of EGFR sensitizing mutations on mortality-risk reduction were observed in all analyses. This finding was consistent with the outcomes of a multicenter study in Thailand, which showed that EGFR-TKI treatment improved the overall survival of patients with EGFR-responsive mutations (Sukauichai et al, 2022;Khiewngam et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Since then, patients with histology of adenocarcinoma were screened for EGFR sensitivity mutations and the drug was made accessible to the patient. Healthcare policy, technologies for investigations, diagnosis, as well as the accessibility to healthcare services have been much improved in the country (Khiewngam et al, 2023).…”
Section: Impact Of Waiting Times On Mortality In Advanced Stagementioning
confidence: 99%